2012
DOI: 10.1103/physrevlett.108.195004
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz Turbulence Associated with Collisionless Shocks in Laser Produced Plasmas

Abstract: We report the experimental results of a turbulent electric field driven by Kelvin-Helmholtz instability associated with laser produced collisionless shock waves. By irradiating an aluminum double plane target with a high-power laser, counterstreaming plasma flows are generated. As the consequence of the two plasma interactions, two shock waves and the contact surface are excited. The shock electric field and transverse modulation of the contact surface are observed by proton radiography. Performing hydrodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Sheared flow settings have been traditionally studied using the MHD framework [12][13][14], where the Kelvin-Helmholtz instability (KHI) is the only instability known to develop [15]. Only very recently have collisionless unmagnetized sheared plasma flows been addressed experimentally [16] and using particle-in-cell (PIC) simulations, revealing a rich variety of electron-scale processes, such as the electron-scale KHI (ESKHI), dc magnetic field generation, and unstable transverse dynamics [17][18][19][20][21][22]. The generated fields and modified particle distributions due to these microscopic processes can strongly impact succeeding macroscopic dynamics of the sheared flow.…”
mentioning
confidence: 99%
“…Sheared flow settings have been traditionally studied using the MHD framework [12][13][14], where the Kelvin-Helmholtz instability (KHI) is the only instability known to develop [15]. Only very recently have collisionless unmagnetized sheared plasma flows been addressed experimentally [16] and using particle-in-cell (PIC) simulations, revealing a rich variety of electron-scale processes, such as the electron-scale KHI (ESKHI), dc magnetic field generation, and unstable transverse dynamics [17][18][19][20][21][22]. The generated fields and modified particle distributions due to these microscopic processes can strongly impact succeeding macroscopic dynamics of the sheared flow.…”
mentioning
confidence: 99%
“…In order to confirm this, we have performed proton radiography to measure the shock electric/magnetic field with the LULI2000 laser facility. We have reported the experimental results of a turbulent electric field driven by KHI associated with two collisionless shock waves (Kuramitsu et al 2012). Due to the laser conditions of LULI2000, the counterstreaming plasmas are not symmetric; they can have different lateral expansions and thus transverse velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent rapid growth of laser technologies allows us to model space and astrophysical phenomena in laboratories (Drake 1999;Remington et al 1999Remington et al , 2006Takabe et al 1999). For instance, collisionless shocks have been experimentally investigated in laser-produced counterstreaming plasmas (Morita et al 2010Kuramitsu et al 2011Kuramitsu et al , 2012Kugland et al 2012;Ross et al 2012;Fox et al 2013;Yuan et al 2013;Huntington et al 2015;Park et al 2015).W efirst reported the relatively laminar density jump with optical interferometry in collisionless counterstreaming plasmas in the absence of an external magnetic field using the Shenguang II laser facility (Morita et al 2010). In order to distinguish shock from contact surface we measured the emission jump and its time evolutions with self-emission optical pyrometry (SOP) with the Gekko XII (GXII) laser facility (Kuramitsu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sorasio et al have shown a possibility of high Mach-number collisionless ES shock formation in counter-streaming plasmas in which temperatures and densities are largely different [89]. Motivated by these predictions [89,90], some authors have studied the latter scheme; the generation of collisionless ES shock in counterstreaming plasmas using double-plane target and one-directional high-energy laser systems [96][97][98][99][100][101]. Morita et al have measured a large density-jump [96], and Kuramitsu et al have shown the temporal evolution of the emission profiles [97].…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments using high-energy laser systems, there are two schemes for the generation of collisionless ES shock. One is an interaction between laser-produced high-density ablating plasma and a low-density ambient plasma [94,95], and the other is an interaction between laser-ablated counter-streaming plasmas using double-plane target [96][97][98][99][100][101].…”
Section: Introductionmentioning
confidence: 99%